2006
DOI: 10.1200/jco.2005.03.4264
|View full text |Cite
|
Sign up to set email alerts
|

BCL2 Expression Is a Prognostic Marker for the Activated B-Cell–Like Type of Diffuse Large B-Cell Lymphoma

Abstract: Treating all DLBCL as a single entity ignores the mechanistic differences in BCL2 upregulation and obscures the prognostic significance of BCL2 expression. Hence, the significance of BCL2 and other biomarkers should be assessed in the context of DLBCL subgroups in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
180
6
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(205 citation statements)
references
References 38 publications
15
180
6
4
Order By: Relevance
“…FOXP1 was also predominantly expressed in a similar subset of DLBCL with positive BCL2 [25]. BCL2 protein overexpression has been reported to occur in 24-66 % of cases of DLBCL [26,27]. It has been postulated that in DLBCL changes in FOXP1 and BCL2 were interdependent and that the presence of an additional copy of FOXP1 gene will cause BCL2 protein to be active [28,29].…”
Section: Follow-up and Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…FOXP1 was also predominantly expressed in a similar subset of DLBCL with positive BCL2 [25]. BCL2 protein overexpression has been reported to occur in 24-66 % of cases of DLBCL [26,27]. It has been postulated that in DLBCL changes in FOXP1 and BCL2 were interdependent and that the presence of an additional copy of FOXP1 gene will cause BCL2 protein to be active [28,29].…”
Section: Follow-up and Survivalmentioning
confidence: 99%
“…Several studies have indicated that the expression of FOXP1 in DLBCL is associated with poor clinical outcome [16, 17, Prognostic value of miR-34a and target proteins in gastric lymphomas 439 [23][24][25]. Previous studies with MALT lymphoma indicate that FOXP1 positivity is confined to MALT lymphomas with poor clinical outcome, polymorphic histology, and high risk of transforming into DLBCL [18,26,27]. The previously described role of miR-34a is as a direct link between the tumor suppressor p53 and the oncogenic protein BCL2 [13,14].…”
Section: Follow-up and Survivalmentioning
confidence: 99%
“…4A). Strikingly, RP lymphomas were found to exhibit significantly higher IkBa expression levels, further accompanied by substantially higher bcl2 expression levels, thus reminiscent of the NF-kB/Bcl2 network analyzed in Figure 3 and of the genetic hallmark lesions detectable in activated B-cell-like (ABC) DLBCL, the prognostically inferior DLBCL subtype characterized by constitutively active NF-kB signaling due to a variety of activating mutations in the NF-kB pathway and by very high Bcl2 transcript levels (Iqbal et al 2006;Lenz et al 2008b;Compagno et al 2009;Staudt 2010;Nogai et al 2011).…”
Section: Oncogenic Network Determine Opposing Roles Of Nf-kb On Treamentioning
confidence: 99%
“…6 Other mechanisms of BCL2 deregulation, more often observed in ABC DLBCLs, include amplification of the BCL2 gene or its transcriptional upregulation through constitutive activation of the nuclear factor-kB pathway. 7 Saito et al 8 reported that the BCL2 promoter can also be aberrantly hypermutated in DLBCL, which may prevent its inhibition by MIZ1 and BCL6. 8 They found a high number of mutations in BCL2 and suggested that the mutations described were the result of somatic hypermutation (SHM).…”
Section: Introductionmentioning
confidence: 99%
“…11 The addition of rituximab to chemotherapy may overcome the impact of BCL2 expression on prognosis; 12 however, BCL2 expression remains relevant when analysis is restricted to specific molecular subtypes of DLBCL. 7,13,14 Indeed, drugs that target BCL2 are being investigated in clinical trials, thus BCL2 mutations may be clinically important in the future.…”
Section: Introductionmentioning
confidence: 99%